LONG TERM FUNCTIONAL EVALUATION AUTOFIBULAR STRUT GRAFT IN CASE OF FRACTURES NECK FEMUR IN RSUD DR SOETOMO SURABAYA - Sjarwani, Achmad; Irsyam, OK Ilham Abdullah (Universitas Airlangga, 2018)
Background: Neck femur fracture has a poor prognosis due to its anatomical structure. Fractures that occur in the elderly often have a heavy comorbid so that the mortality rate in 1 year in this case reaches 30-50%. The techniques that have been developed at this time are not satisfactory results with non-union rate of about 30%.Purpose: Assessing the long-term effectiveness of fibular auto strut graft techniques for neck femoral fracture therapy.Methods: The study was conducted retrospectively using primary data in the form of clinical evaluation and secondary data in the form of medical record data and questionnaires of neck femur fracture patients who performed non-vascularized autofibular strutgraft therapy in the period January 2005 to August 2015 in operating room IRD RSUD Dr. Soetomo Surabaya. Patients were evaluated with Harris Hip Score.Result: Medical record data shows that surgery was performed in January 2005 until August 2015 in the IRD hospital operating room. Soetomo Surabaya with 15 patients that fit criteris inclusion. The final result of Harris Hip Score is excellent in 66.66% of patients, good in 20% of patients, and poor on 13.33% of patients. It can be seen that in large part, the technique of autofibular strutgraft (Surabaya Technique) gives good results to the sufferer.Conclusion: Autofibular strutgraft and reinforcement with cancellous lag screw on neck femur fracture can generally provide good functional results in long term evaluation. From the assessment of functional aspects, abnormal anatomical conditions, and Range of Motion (ROM), obtained satisfactory results. This supports autofibular strutgraft as a neck femur fracture therapy as a major therapeutic option at a young age.